Social Entrepreneurship in Peasants and Its Impact on Agriculture in Kazakhstan - Bezheneyeva, Saniya; Pirandy, Gusti (Talenta Publisher, 2024)
Social entrepreneurship integrates economic and social objectives to empower peasants through sustainable innovation, improve productivity, welfare and food security, and address agrarian challenges in Kazakhstan. This research seeks to understand the concept and practice of social entrepreneurship among peasants in Kazakhstan and its impact on the agricultural sector. The method used is an exploratory descriptive qualitative approach. Data collection techniques through literature study. Data were collected from secondary sources such as books, academic journals, research reports, and articles related to social entrepreneurship, sustainable agriculture, and policies in Kazakhstan. The data analysis technique used was thematic analysis. Social entrepreneurship plays an important role in the agricultural sector in Kazakhstan by offering innovative solutions to improve productivity, peasant welfare and environmental sustainability. This approach helps overcome barriers such as technological limitations, training, and the impacts of climate change, and encourages the adoption of efficient and sustainable farming methods. Through peasant empowerment and community collaboration, social entrepreneurship strengthens peasants' economic resilience and bargaining position in the global market. The integration of environmentally friendly practices and optimization of local resources also improves the social welfare and sustainability of the agricultural sector, making it more adaptive to future challenges. This research supports Kazakhstan's agricultural sector development policy.